“Integration of health teams and the community”: Speech delivered at the Universidad Nacional y Popular de Buenos Aires - Mario Testa (Salud Colectiva, 2025)
In this speech, delivered at the inaugural class of the pre-medical course at the Faculty of Medicine of the Universidad Nacional y Popular de Buenos Aires, in 1973, Mario Testa presents a profound critique of the educational model inherited from the liberal oligarchic project, marked by individualism, superficiality, and detachment from the country’s reality. He calls for a comprehensive transformation of the university, aimed at dismantling its feudal structure and building an institution committed to the social and political needs of the nation. Confronting the traditional medical model grounded in prestige, power, and competition, Testa advocates for a new conception of medicine as a collective and solidarity-based practice, embedded in a national and popular project. He emphasizes the need to form health teams integrated with the community, where physicians no longer occupy a central role but instead become one more worker in a collective process focused on solving the people’s problems. Finally, he asserts that the Faculty of Medicine, transformed into a Faculty of Health Sciences, must be guided by social medicine, in order to train professionals committed to teamwork, critical thinking, and active participation in the construction of a more just country.